2019 IEEE International Symposium on Information Theory (ISIT) 2019
DOI: 10.1109/isit.2019.8849825
|View full text |Cite
|
Sign up to set email alerts
|

Private Polynomial Computation for Noncolluding Coded Databases

Abstract: Private computation in a distributed storage system (DSS) is a generalization of the private information retrieval (PIR) problem. In such setting a user wishes to compute a function of f messages stored in noncolluding coded databases while revealing no information about the desired function to the databases. We consider the problem of private polynomial computation (PPC). In PPC, a user wishes to compute a multivariate polynomial of degree at most g over f variables (or messages) stored in multiple databases.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 29 publications
(220 reference statements)
0
19
0
Order By: Relevance
“…upload constraints [46], arbitrary collusion patterns [21], [47], single server PIR with user side information [48]- [54], latent-variable single server PIR [55], as well as applications of PIR to private computation [56]- [59], private search [60], private set intersection [45], coded computing [61], locally decodable codes [62], etc.…”
Section: Introductionmentioning
confidence: 99%
“…upload constraints [46], arbitrary collusion patterns [21], [47], single server PIR with user side information [48]- [54], latent-variable single server PIR [55], as well as applications of PIR to private computation [56]- [59], private search [60], private set intersection [45], coded computing [61], locally decodable codes [62], etc.…”
Section: Introductionmentioning
confidence: 99%
“…This problem is referred to as Private Computation (PC), which seeks efficient solutions for the user to compute a function of files stored at distributed servers, without disclosing the identity of the desired function to the servers. The PC problem was firstly introduced in [12], [20] and has attracted remarkable attention in the past few years within information-theoretic community [9], [13], [15], [16]. In the classical PC setup, the user wishes to compute one out of any ξ candidate functions over M files from N non-colluding servers, each of which stores all the M files, while preventing any individual server from obtaining information about which function is being computed.…”
Section: Introductionmentioning
confidence: 99%
“…−1 . Moreover, they [15] further constructed PLC schemes on arbitrary linear storage codes and showed that the capacity of MDS-PLC can be achieved for a large class of linear codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In [10] the capacity for private linear computation in MDS coded databases is studied. Recently the new problem of retrieving a polynomial function of files from some servers has been introduced and discussed in [11] and [12] by using Lagrange encoding in coded databases.…”
Section: Introductionmentioning
confidence: 99%